2016
DOI: 10.1007/s00426-016-0749-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of practice and strategy in mental rotation training: transfer and maintenance effects

Abstract: Research in the domain of spatial abilities is now focusing on whether spatial abilities can be trained, and whether this can produce gains and maintenance effects in other, untrained skills. The aim of the present study was to assess the benefit and maintenance effects of two types of mental rotation training, one based on mental rotation practice alone, the other combining mental rotation practice with the use of a spatial (rotation) strategy. Seventy-two females took part in the study: 24 practiced with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 47 publications
6
44
0
Order By: Relevance
“…Another point worth highlighting from this present study is the adaptation we performed of the original task by Quaiser-Pohl (2003) , with the objective of evaluating the effect of MR training on 3 year-old children. In addition, the evaluation of the training program with a different task than that used during training supports the idea of knowledge transfer of spatial skills ( Terlecki et al, 2008 ; Uttal et al, 2013a ; Meneghetti et al, 2016a , b ). In this regard, the earlier work of Marmor (1977) , Ehrlich et al (2006) , and Krüger et al (2014) did not assess transfer, as their training task was the same as their assessment test.…”
Section: Discussionmentioning
confidence: 66%
“…Another point worth highlighting from this present study is the adaptation we performed of the original task by Quaiser-Pohl (2003) , with the objective of evaluating the effect of MR training on 3 year-old children. In addition, the evaluation of the training program with a different task than that used during training supports the idea of knowledge transfer of spatial skills ( Terlecki et al, 2008 ; Uttal et al, 2013a ; Meneghetti et al, 2016a , b ). In this regard, the earlier work of Marmor (1977) , Ehrlich et al (2006) , and Krüger et al (2014) did not assess transfer, as their training task was the same as their assessment test.…”
Section: Discussionmentioning
confidence: 66%
“…Although many studies have shown that practicing mental rotation can lead to an improvement in spatial reasoning skills (Cohen & Hegarty, 2007;Hoyek, Collet, Di Rienzo, De Almeida, & Guillot, 2014;Meneghetti, Borella, & Pazzaglia, 2016;Meneghetti, Cardillo, Mammarella, Caviola, & Borella, 2017;Rodán, Contreras, Elosúa, & Gimeno, 2016), these studies do not always use optimal methods for reliably detecting training effects (see Uttal et al, 2013, for review). Optimal methods include active control groups in which the control training task has levels of difficulty similar to those of the experimental task (Simons et al, 2016).…”
Section: Training In Mental Rotation Skillsmentioning
confidence: 99%
“…Furthermore, it is important to use novel stimuli throughout training and at test to rule out improvements in performance due to familiarity with repeated stimuli (Tarr & Pinker, 1989). The majority of previous mental rotation training studies have used threedimensional (3D) cubes similar to those used in the current study (Cohen & Hegarty, 2007;Meneghetti et al, 2017). Some studies have used 3D stimuli that more directly apply to everyday life, such as human anatomy (Hoyek et al, 2014) or a combination of 3D cubes and 2D drawings (Meneghetti et al, 2016;Rodán et al, 2016).…”
Section: Training In Mental Rotation Skillsmentioning
confidence: 99%
“…Strategy selection pertaining to spatial reasoning has been extensively studied in the mental rotation literature (Hegarty, 2010;Khooshabeh, Hegarty, & Shipley, 2013;Kozhevnikov, Hegarty, & Mayer, 2002;Meneghetti, Cardillo, Mammarella, Caviola, & Borella, 2016;Shepard & Metzler, 1971;Ter Horst, Jongsma, Janssen, van Lier, & Steenbergen, 2012). For several decades' researchers investigating strategy selection during spatial thinking tasks have attempted to operationalize the strategies that participants' use, but an inconsistent vocabulary has been employed.…”
Section: Strategy Selection Versus Flexibility: Using Eye-trackers Tomentioning
confidence: 99%